2021
DOI: 10.1007/s13760-021-01630-4
|View full text |Cite
|
Sign up to set email alerts
|

Headache and migraine in mitochondrial disease and its impact on life—results from a cross-sectional, questionnaire-based study

Abstract: Headache is frequent in patients with mitochondrial disorders. Previous studies point to a higher prevalence of headache in these patients than in the general population. As mitochondrial disorders often present a variety of other symptoms, the question arises how much the presence of headache really influences daily life. We performed a cross-sectional, questionnaire-based study investigation with 61 patients with a genetically proved mitochondrial disease mainly composed of CPEO phenotype. Headache was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Headaches account for one of the five most debilitating symptoms of mitochondrial diseases ( 6 ). Headaches, especially migraine, have a substantial impact on social functioning and everyday life in patients with mitochondriopathies ( 5 ). However, both, acute as well as a preventive treatment for migraine in patients with mitochondrial disease are challenging—data on the use and efficacy of medication are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Headaches account for one of the five most debilitating symptoms of mitochondrial diseases ( 6 ). Headaches, especially migraine, have a substantial impact on social functioning and everyday life in patients with mitochondriopathies ( 5 ). However, both, acute as well as a preventive treatment for migraine in patients with mitochondrial disease are challenging—data on the use and efficacy of medication are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…involvement as well as neurological symptoms, such as epileptic seizures, ataxia, and headache (1). The presence of migraine with and without aura and other headache disorders, such as tension-type headaches, is well described in mitochondrial diseases, such as chronic progressive external ophthalmoplegia (CPEO), myoclonic epilepsy with ragged-red fibers (MERRF) and mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome (2)(3)(4)(5). Headache prevalence in this patient group seems to be higher than in the general population (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified different cut-off values of the two biomarkers for mitochondrial disease in children, young adults, and adults [ 14 , 15 , 16 ]. Even considering the different kits for the determination of the biomarkers, the values especially for GDF-15 in this study were markedly below the cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…From the epidemiologic point of view, several studies show a higher prevalence of migraine than expected in patients with a genetically proved mitochondrial disorder such as MELAS, MERRF (myoclonic epilepsy with ragged red fibers) and LHON (Leber’s hereditary optic neuropathy) [ 11 , 12 , 13 , 14 ]. Migraine is a substantial contributor for burden of disease in patients with mitochondrial diseases [ 15 ]. However, in genetic analyses, none of the frequent point mutations of the mitochondrial DNA, e.g., m.3243 A > G associated with the MELAS-syndrome, in patients with migraine with aura were detected [ 16 ].…”
Section: Introductionmentioning
confidence: 99%